Our results of intravitreal ranibizumab injections for age related macular degeneration - Turgut, Burak; Kasar, Kader; Bilir Can, Nagehan; Çeliker, Ülkü (My University, 2012)
Purpose: To evaluate the results of three doses of intravitreal ranibizumab injection in patients with choroidal neovascularization secondary to age-related macular degeneration. Materials and Methods: Between January 2009 to February 2011, 33 patients (39 eyes) were included the study. The patients were performed three doses of intravitreal injections of ranibizumab who had leakage in fundus fluorescein angiography (FA), intraretinal and subretinal fluid and active choroidal neovascular membrane (CNV) in optical coherence tomography (OCT). Patients were applied to three doses of 0.1 cc (0.5 mg) intravitreal ranibizumab injection with an interval of four weeks. Before the injection and 3, 6 months after the injection, visual acuity (log-MAR), anterior segment, fundus, OCT and FA were evaluated. Statistical analysis was performed using the SPSS 12 program. Results: 19 patients (57.7%) male and 14 (43.3%) were female. The mean age of 71.4±7:45 (60-85), respectively. The mean visual acuity (according to log-MAR) of the patients before treatment 1.27±0.68 3 months after treatment visual acuity, 1.07±0.48, 6 months atfter treatment, visual acuity, 1.04±0.45, respectively. The best visual acuity was increased in 21 eyes, but was not changed in eight eyes after ranibizumab injection of three doses. Leakage was found to be decreased at 10 eyes. Three months after the injection, 21 eyes (53.8%) had reduced leakage, 18 eyes (46.2%) had continued to leakage at FFA photographs. Six months after the injection, the leakage was not seen in 25 eyes (%64.1), 10 eyes (%25.6) had a new leakage and 4 eyes (%10.2) was not changed. Three months after the injection intraretinal and subretinal fluid was reduced at 30 eyes (76.9%), there was no fluid in 24 eyes (%61.5) and there was minimal fluid in 15 eyes (%38.5) at six months. Conclusion: We observed prevention of vision loss as well as improvement of mean visual acuity at early-term outcome analysis, in patients with three doses of intravitreal ranibizumab injection for choroidal neovascularization secondary to age-related macular degeneration.
Yaşa ba?li maküla dejeneresansinda i?ntravitreal ranibizumab enjeksiyonu sonuçlarimiz
Keywords: Age-related macular degeneration; Ranibizumab